2005
DOI: 10.1111/j.1095-8339.2005.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

The genus Rosa (Rosoideae, Rosaceae) revisited: molecular analysis of nrITS-1 and atpB-rbcL intergenic spacer (IGS) versus conventional taxonomy

Abstract: The genus Rosa (Rosoideae, Rosaceae) revisited: molecular analysis of nrITS-1 and atp B-rbc L intergenic spacer (IGS) versus conventional taxonomy Sequences of the nrDNA internal transcribed spacer 1 (nrITS-1) and atp B-rbc L intergenic spacer (IGS) of the cpDNA were analysed for all sections of the genus Rosa L. (Rosoideae, Rosaceae) to study molecular infrageneric taxonomy and relationships of Rosa with respect to conventional taxonomy based upon morphological and anatomical data as well as phytochemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
102
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 38 publications
22
102
2
Order By: Relevance
“…4 and 5). This relationship was also recovered in previous studies (Bruneau et al, 2007;Fougère-Danezan et al, 2015;Meng et al, 2011;Qiu et al, 2012;Wissemann and Ritz, 2005). Our phylogenies showed that these species together are not monophyletic, and chloroplast phylogeny resolved R. lucidissima as the earliest divergent species in the Asian subclade.…”
Section: Phylogeny Of Rosa Sections Chinenses and Synstylaesupporting
confidence: 87%
See 1 more Smart Citation
“…4 and 5). This relationship was also recovered in previous studies (Bruneau et al, 2007;Fougère-Danezan et al, 2015;Meng et al, 2011;Qiu et al, 2012;Wissemann and Ritz, 2005). Our phylogenies showed that these species together are not monophyletic, and chloroplast phylogeny resolved R. lucidissima as the earliest divergent species in the Asian subclade.…”
Section: Phylogeny Of Rosa Sections Chinenses and Synstylaesupporting
confidence: 87%
“…Though this study focused on sections Chinenses and Synstylae, our extensive sampling did help understanding relationships within the whole genus. As previous studies found (Bruneau et al, 2007;Wissemann and Ritz, 2005;Wu et al, 2000), none of our three phylogenies (Figs. 1-3) supported traditional taxonomy of subgenera and sections (Rehder, 1940;Wissemann, 2003).…”
Section: Phylogeny Of Rosa Sections Chinenses and Synstylaesupporting
confidence: 68%
“…Five of the seven major wild ancestors of garden roses (Wylie 1954) were also sampled in this study. Because the phylogenetic relationships among species of Rosa have not yet been fully resolved (Wissemann and Ritz 2005;Bruneau et al 2007), 30 species of Rosa in total were sampled to avoid missing the real parental species, covering eight of the ten sections of subgen. Rosa and one species from subgen.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The barriers to gene flow among Rosa L. species are weak (Atienza et al 2005), and hybridization has contributed greatly to species diversity of this genus (Rehder 1940;Wissemann and Ritz 2005). Numerous fertile interspecific rose hybrids have been reported (Fagerlind 1944(Fagerlind , 1951(Fagerlind , 1958Grustafsson 1944;Lewis and Basye 1961;Roberts 1977;Atienza et al 2005;Bruun 2005;Mercure and Bruneau 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Rosa consists of a highly complex and much-debated phylogeny, divided into four subgenera, of which subgenus Rosa comprises over 95% of all species (Wissemann and Ritz, 2005). Rosa is generally divided into ten sections, four of which (Synstylae, Gallicanae, Indicae and Pimpinellifoliae) have contributed to the domesticated rose genepool .…”
Section: Genetic Mapping In Rosementioning
confidence: 99%